الكفاءة الاقتصادية لاستخدام مياه الجفت في تسميد أشجار الزيتون في محافظة اللاذقية - جحجاح محسن; هيفا سوسن; احسينه علي (Latakia University Journal -Biological Sciences Series, 2017)
يهدف البحث إلى دراسة الكفاءة الاقتصادية لاستخدام مياه الجفت في تسميد أشجار الزيتون , حيث شملت عينة البحث /294/ مزارعاً في محافظة اللاذقية بالاعتماد على المنهج الوصفي التحليلي , وتوصلت النتائج إلى أن تسميد أشجار الزيتون بمياه الجفت ذو ريعية انتاجية عالية , حيث يحقق ربحاً صافياً قدره (33668) ل.س/دونم/سنة بينما بلغ هامش الربح الإجمالي نحو (61235) ل.س ومعامل الربحية قياساُ إلى تكاليف الانتاج نحو(41.32%)%، بينما بلغ معامل الربحية قياسا الى راس المال المستثمر نحو 42.98%. The research aims to study the economic efficiency of olive mill wastewater (OMWW) use in fertilizing olive trees, Which included research sample / 294 / farmer in Lattakia Governorate, depending on the descriptive analytical method,And found the results to be to fertilize the olive trees with (OMWW) rents high productivity, Where it posted a net profit of (33,668) SP / acre / year, while gross margin stood at (61 235) SP , The coefficient of profitability compared to the cost of production (about 41.32%)%, while the profitability coefficient was compared to the capital invested approximately 42.98%.